Lingkup Regulasi Media dalam Lanskap Global - Pandan Yudhapramesti (Balai Pengembangan SDM dan Penelitian Komunikasi dan Informatika (BPSDMP Kominfo) Banjarmasin, 2016)
The use of media in a variety of platforms, continues to increase globally. As it is, many problems arise, such as the increase in cyber crime, the number of lawsuits as well as an increase in people who are subject to the penalties for actions in the cyber world. This paper is the result of literature research on the study of media regulation trends. The focus of research aimed at: a) Current issues related to media policy in the global landscape, b) Trends on research issues of media studies, and c) an alternative method in the study of media regulation. The focus of research directed its relevance to the context of Indonesia. The study concluded that study of media regulation should aim to understand the current issues in the media, including efforts to find ideas solutif due to the development of a multi-dimensional global landscape, as well as issues that arise as a result of the user interaction media between the state and the nations. Trends issue generally highlighted are: 1) The policy of media, freedom of expression and citizenship, 2) media policy and institutional design, 3) media policy and the state media, as well as 4) the problems arising from the transformation of technology and global interactions. Recent developments in the media and global digital landscape has prompted numerous new problems, thus demanding the emergence of alternative methods, such as method of comparison or comparative studies and policy analysis method is based on a system perspective. Keywords: Media Studies, Media Policy, The Digital Era, Global Era ABSTRAK Penggunaan media dalam berbagai platform, terus meningkat secara global. Seiring hal tersebut, berbagai masalah muncul, seperti peningkatan kejahatan siber, jumlah tuntutan hukum serta peningkatan orang yang dikenai hukuman akibat tindakan di dunia siber. Makalah ini merupakan hasil penelitian kepustakaan mengenai tren kajian regulasi media. Fokus penelitian diarahkan pada: a) persoalan-persoalan mutakhir terkait kebijakan media dalam lanskap global, b) Tren tentang isu-isu penelitian kajian media, serta c) Metode alternatif dalam kajian regulasi media. Fokus penelitian diarahkan relevansinya kepada konteks Indonesia. Kajian ini menyimpulkan bahwa, kajian regulasi media perlu diarahkan untuk memahami persoalan mutakhir pada media, termasuk upaya menemukan gagasan solutif akibat perkembangan multi dimensi dalam lanskap global, serta persoalan yang muncul akibat interaksi pengguna media antar negara dan bangsa. Tren isu yang umumnya disoroti adalah: 1) Kebijakan media, kebebasan berekspresi (freedom of expression) dan citizenship, 2) kebijakan media dan desain institusional, 3) Kebijakan media dan media pemerintah, serta 4) masalah-masalah yang muncul akibat transformasi teknologi dan interaksi global. Perkembangan mutakhir media dalam lanskap digital dan global telah memunculkan berbagai persoalan baru, sehingga menuntut lahirnya metode-metode alternatif, seperti metode perbandingan atau studi komparasi serta metode analisis kebijakan berdasarkan perspektif sistem. Kata kunci: Kajian Media, Kebijakan Media, Era Digital, Era Global